Analisa Karakteristik Getaran Pada Mesin Asphalt Mixing Plant Tipe Apollo ANP- 1500 Berdasarkan Kapasitas Pembuatan Aspal Jalan Pada Daerah Horizontal, Vertikal Dan Longitudinal Berdasarkan Time Domain - Sihombing, Suriady; Nababan, Wilson; Sidabutar, Ros Anita; Saragi, Yetty Riris; Lumbangaol, Partahi; Simanjuntak, Salomo (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
Asphalt mixing plant machine is a tool used to process several materials into road asphalt, where it is necessary to know how to analyze the vibration characteristics of the asphalt mixing plant machine based on the capacity of making asphalt road in horizontal, vertical and longitudinal areas based on the time domain. The research method is carried out by collecting data on the amount of deviation, speed and acceleration that arise due to the processing of several materials so as to produce road asphalt based on differences in the capacity of different asphalt processed. Based on the measurement results, it is found that the highest vibration occurs at the asphalt mixing plant machine seat for a capacity of 60 tons/hour where the magnitude of the deviation is 0.222 mm in the horizontal direction at 100 seconds, the largest velocity is 11.99 mm/s horizontally in the second 40 mm/s and the largest acceleration is 369.7 mm/s2 in the horizontal direction of the 20th second. According to the ISO IS 2372 standard, the vibration of the Apollo ANP-1500 asphalt mixing plant machine enters class IV with a generator capacity above 75 KW, to be more precise (150KVA = 120KW). Then it can be analyzed that the generator vibration falls into the category of "vibration within tolerance limits and is only operated for a limited time" where the highest speed is 11.99 mm/s.